Effects of particle size upon surface roughness and wall friction during compaction of Labisia pumila tablets - Etti, Christopher Joseph; Yusof, Yus Aniza; Chin, Nyuk Ling; Aziz, Mohammad Gulzarul (Faculty of Engineering, Universiti Putra Malaysia, 2012)
The influence of particle size upon surface roughness and wall friction of Labisia pumila powder extracts during tablet compaction was studied. Labisia pumila is a popular Malaysian herb known for the treatment of postpartum mothers, gonorrhoea, rheumatism, pile and bone diseases. Powder materials are known for tablets formation suitable for usage as oral dosage when subjected to mechanical forces. These tablets are known to be influenced by friction between powder particles, and the wall of compacting vessel. A universal testing machine with forces ranging from 5.0 to 10.0 kN ± 0.1kN with a compression speed of 5 mm min-1 was used to compact the herb using a 13- mm- diameter cylindrical stainless steel uniaxial die. During compression, tablet strength was directly proportional to compaction pressure and inversely proportional to particle size. The surface roughness of Labisia pumila compacted tablets increased with increase in particle size of powder extract, and the bottom surfaces of tablets were rougher than the upper surfaces. The tablet strength increased with a decrease in wall friction. From the compaction models, 0.4g of powder was most compressible and easiest to deform into tablets compared with 0.6g and 0.8g of powders upon uniform loads. Generally, particle size and wall friction are seen to influence the surface roughness and tablets strength.